Comparative evaluation of the effect of Ocimum sanctum and metformin on serum lipid profile in high fat diet fed diabetic rats - Mishra, Shailendra; Ahmed, Quazi Shahir; Sayedda, Kauser (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Dyslipidaemia is an important risk factor for development of macrovascular complications in type 2 diabetes mellitus. Ocimum sanctum (OS) and metformin have shown to have antihyperlipidaemic effects. The present study was undertaken to evaluate the effects of OS and Metformin on body weight & plasma lipid levels of high fat diet fed diabetic rats Methods: Total of 30 male wistar rats (100-150gm) were obtained. Animals were fed with a high fat diet throughout the study (6 weeks). Diabetes was induced by using single intra-peritoneal injection of Streptozotocin 50mg/kg at the end of 4 weeks. Diabetic rats were divided into groups of 6 each and treated as follows: Group 1- Diabetic control, was given vehicle orally. Group 2- O.S. ethanolic extract 100mg/kg body weight orally for 14 days. Group 3- O.S. ethanolic extract 200mg/kg body weight orally for 14 days. Group 4- Metformin 100mg/day for 14 days Results: At the end of 4 weeks, body weight of rats were significantly increased (p <0.05). Maximum weight gain was seen in control group whereas weight gain was least in O.S. 200mg/kg group (p >0.05). Decrease in body weight was seen in metformin group. Abdominal circumference of rats also showed similar pattern (p >0.05). OS 200 caused significant reduction in serum LDL levels (p <0.05) and significant rise of serum HDL levels (p <0.05) as compared to control group. Metformin also favourably affected the lipid profile and its effects were not significantly different from effects of OS 200 (p> 0.05). Conclusions: Present study revealed that Ocimum Sanctum caused significant reduction in serum lipid levels in high fat diet fed diabetic rats. Metformin also exhibited antihyperlipidaemic activity. So, it is concluded that OS or metformin alone or in combination could be a novel adjunct to diet and life style modification for the management of dyslipidaemia in type 2 diabetes. Further studies are required to confirm the antidyslipidaemic activities of individual phytoconstituents of Ocimum sanctum.